Broad Money Demand and Asset Substitution in China - Wu, Ge (IMF Working Papers; Working Paper ;, 2009)
Recent changes to China's financial system, in particular ongoing interest rate liberalization, gradual movement toward a more flexible exchange rate regime, and rapid development of capital markets, have changed substantially the environment in which monetary policy operates. In light of these changes, we estimate an error correction model using a General-to-Specific methodology and confirm that a stable broad money demand function exists taking proper account of asset substitution, with an income elasticity of less than unity. Current inflation is found to have a significant negative impact on the real money demand. However, money demand does not appear very sensitive to interest rates, possibly reflecting their partial liberalization. Changes in the exchange rate also do not affect money demand significantly, but expectations of a further renminbi appreciation since 2005 appears to induce more money demand. Stock prices are statistically insignificant despite recent investors' interest in equity markets.